Neighbour effects of purslane (Portulaca oleracea L.) on Cd bioaccumulation by soybean in saline soil - A. Ashrafi; M. Zahedi; K. Fahmi; R. Nadi (Plant, Soil and Environment, 2014)
Bioaccumulation of heavy metals can be affected by various crop-weed interactions in agroecosystems. An experiment was conducted to evaluate the role of belowground interaction of soybean and purslane (Portulaca oleracea L.) weed on cadmium (Cd) uptake and its allocation to soybean grains. The experimental treatments included two cropping systems (mono and mixed culture), two salinity levels (0% and 0.5% NaCl) and three levels of Cd in soil (control; 3 and 6 mg Cd/kg). Results showed that the promoting effect of salinity on Cd uptake by soybean and Cd allocation to grains was enhanced in the presence of purslane compared to the absence of neighbour plant. This could be due to increasing Cd-mobilization within the shared rhizosphere of plants. In the non-saline soil decreasing uptake and grain allocation of Cd in co-planted soybean was associated with enhancing of purslane Cd uptake and the depletion of Cd in soil solution. Therefore, it can be concluded that co-planted purslane can alter the uptake of cadmium to the neighboring soybean plants; its effect may be influenced by soil environmental conditions such as salinity.